2010
DOI: 10.1016/j.neulet.2009.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Postembryonic development of sexually dimorphic glomeruli and related interneurons in the cockroach Periplaneta americana

Abstract: In most insects, sex pheromone is processed by an enlarged glomerular complex (macroglomerular complex, MGC) in the male antennal lobe (first-order olfactory center). The MGC of the American cockroach consists of two closely located A- and B-glomeruli which are responsible for processing the major sex pheromone components, periplanone-A and -B, respectively. Using anterograde dye injection, we investigated sexual dimorphism in sensory afferents and interneuron. The A- and B-glomeruli exist in the first larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…The orientation and position of the brain is shown with reference to the body axis, which is more convenient when working with appendages (Nishino et al, 2009, 2010, 2011). The coordinates based on the neuraxis used in some of previous studies on the cockroach brain were converted to body axis coordinates in this work.…”
Section: Methodsmentioning
confidence: 99%
“…The orientation and position of the brain is shown with reference to the body axis, which is more convenient when working with appendages (Nishino et al, 2009, 2010, 2011). The coordinates based on the neuraxis used in some of previous studies on the cockroach brain were converted to body axis coordinates in this work.…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for staining antennal afferents were described previously (Nishino and Mizunami, 2007;Nishino et al, 2009aNishino et al, , 2010. After the animals had been anesthetized with carbon dioxide, the head with antennae was detached from the body and fixed on a dish with low-melting-point wax.…”
Section: Procedures For Staining Antennal Afferentsmentioning
confidence: 99%
“…In the cockroach, anterograde staining of antennal sensory afferents showed that the sensory axon terminals ramify throughout the glomerulus, making synaptic connection with projection neurons and local interneurons (Boeckh and Tolbert, 1993;Distler and Boeckh, 1997a,b), whose dendritic trunks enter from the periphery (Malun et al, 1993). In the cockroach, a hemimetabolous insect, the basic structure of the AL is formed during embryogenesis (Salecker and Boeckh, 1995), with the volume of individual glomeruli increasing during postembryonic development (Prillinger, 1981;Nishino et al, 2009aNishino et al, , 2010: axon terminals of newly emerged sensory afferents are assumed to be added in the proximal region to the axonal entry side of each glomerulus at every molt (Nishino and Mizunami, 2007). However, in holometabolous insects, such as moths, honeybees, and flies, the axons of olfactory receptor neurons enter the AL at the beginning of pupal ecdysis, and they grow first along the periphery of the glomerular precursor structure and then proceed toward the center (Salecker and Malun, 1999).…”
Section: Different Organization Of Glomeruli Among Different Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ablation of the largest chemosensory organs, antennae, resulted in a delay in ootheca production compared to that in intact females, although complete ablation of the antennae may have side-effects related to loss of sensory input [34]. Unexpectedly, a typical female-specific odor, the primary sex pheromone component (periplanone-B), did not promote ootheca production, despite the fact that the female P. americana is equipped with a specific olfactory glomerulus in its first-order olfactory center that processes periplanone-B [35, 36]. …”
Section: Discussionmentioning
confidence: 99%